Answer: -1 < x < 3
===========================================================
Step-by-step explanation:
The first thing to do is to swap the positions of the x < 3 and the x > -1
So you'll end up with x > -1 and x < 3
Now focus entirely on x > -1. Swap the left and right sides, and also swap the inequality sign. So we end up with -1 < x
That means the "x > -1 and x < 3" is the same as "-1 < x and x < 3"
From here, we collapse the two inequalities to form the compound inequality -1 < x < 3
We can say "x is between -1 and 3, excluding either endpoint".